Pandangan Sosiolog dalam Mengatasi Kriminalitas di Kalangan Mahasiswa Pada Kawasan Padat Penduduk - Wahyu Kurniawan Harly Pratama; Sulismadi Sulismadi (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
Behavior or action becomes a benchmark for a peace or peace can be created in an area, Malang City, the increasing number of years makes the population continue to grow, especially in the increase in the number of students at every state university and private university in Malang City. The increase in population is either from the original residents of Malang who carry out the marriage process and produce offspring or increase due to migrants who enter the City / District. Malang for various purposes. With the increase in population, it certainly gives an idea of how the impact on the area, especially in the behavior that exists in densely populated areas, this behavior can be in accordance with the norms, values and laws that apply in the area, but there are also behaviors that are not in accordance with the norms, values and laws that cause unrest in the area, especially in terms of crime. The method in this research uses a descriptive qualitative method with a case study approach. This research was conducted in Bareng Village, which is located in Klojen District, Malang City. The technique of determining informants in this study used purposive sampling technique, namely determining informants with certain criteria. In this case, of course, humans become a benchmark for how the existing order can run smoothly or can be disrupted and also hampered.